Increasing Marketing (Distribution) Of Isal Cookies Msmes Products Using The Whatsapp Application - Rokan, Mustapa Khamal; Az-Zahra, Jihan Syahlina; Putri, Saidina (Universitas Islam Negeri Sumatera Utara, 2023)
Marketing development is one of the main challenges faced by Micro, Small and Medium Enterprises (MSMEs) in improving competitiveness and reaching a wider market. The article used a situational approach from a community service program, which aims to improve the marketing and distribution of Isal Cookies MSMEs products through the use of the WhatsApp application. The strategy used by the author is the data collection method, which is to collect information from the population and samples that have been selected directly. Through hands-on training and mentoring, this program helps businesses understand and optimize the use of WhatsApp Business as an effective marketing tool. These activities include setting up business profiles, managing product catalogs, and communication strategies with customers. The results of this activity show that the utilization of WhatsApp Business can improve marketing efficiency and product distribution, as well as expand market reach. This approach is expected to be a model that can be adopted by other MSMEs to utilize technology to improve their business performance.